THE INFLUENCE OF WORK DISCIPLINE AND WORK ENVIRONMENT ON ORGANIZATIONAL COMMITMENT EMPLOYEE OF SBU ENERGY AT PT BIRO KLASIFIKASI INDONESIA (PERSERO) NORTH JAKARTA - Susita, Dewi; Muslimah, Wahiddah; Waspodo, Agung AWS (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of this research are: 1) To know the description for the work dicipline, work environment and organizational commitment employee of SBU Energy at PT Biro Klasifikasi Indonesia (Persero) North Jakarta, 2) To know the influence work dicipline on organizational commitment employee of SBU Energy at PT Biro Klasifikasi Indonesia (Persero) North Jakarta, 3) To know the influence work environment on organizational commitment employee of SBU Energy at PT Biro Klasifikasi Indonesia (Persero) North Jakarta, 4) To know the influence work dicipline and work environment on organizatonal commitment employee of SBU Energy at PT Biro Klasifikasi Indonesia (Persero) North Jakarta. This research is taken 70 emplooyee of SBU Energy at PT Biro Klasifikasi Indonesia (Persero) North Jakarta, Jakarta. The technique of data collection used method by distributing questionnaires, which then processed with program SPSS version 21.0. this research using descriptive analysis and explanatory. The result of regression shows that there is positive and significant influence work dicipline on organizational commitment, there are positive and significant influence work environment on organizational commitment.